Research and Development (R&D) Interactive Media That is Effective, Efficient and Fun for Students - Marwan Toni; Mahmudin Sudin (Asian Journal of Social and Humanities, 2024)
This development innovation is an effort to overcome the limitations of Islamic religious education teaching materials in schools and increase students' enthusiasm for learning by using interactive media with the help of Android forms. The approach taken in the research and development of teaching media is qualitative and quantitative. This development uses the ADDIE model (analyse, Design, Development, Implementation, and Evaluation), which consists of stages: (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation as procedures and guidelines for developing teaching materials data collection techniques by distributing surveys to test subjects and a series of formative assessments. Analysis techniques use qualitative and statistics. The results of the analysis of the development of teaching materials are in the form of software products or applications in the form of Android. Based on the validation and test results of design experts, 86% said that this product is valid and efficient; the validation results of media experts, 87% of these products are valid and efficient, and the results of material expert validation say 80% of these products are valid and efficient